Impacts of the Fukushima Nuclear Accident on Fish and Fishing Grounds - Nakata, Kaoru; Sugisaki, Hiroya (Springer Nature, 2015)
Fish & Wildlife Biology & Management; Ecology; Environmental Monitoring/Analysis